Railroad noise affected by downward refraction and turbulence - Gołębiewski, R.; Makarewicz, R. (Archives of Acoustics, 2002)
For downward ray bending (temperature inversion and/or downwind propagation) geometrical spreading is principally affected by atmospheric turbulence. Additionally, the variations of rolling stock and train speed occur. Thus, the sound exposure level, LAE, changes from train to train and the equivalent continuous A-weighted sound pressure level of railroad noise, LAeqT, changes from day to day. As such, the mean, LAeqT, is important environmental noise characteristics. The simplified model of noise generation and propagation is derived. It makes possible to calculate LAeqT. Two adjustable parameters of the model are estimated from measurements of the sound exposure level, LAE.